2023
DOI: 10.1109/access.2023.3243081
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation of Fractional-Order Chaotic Power System Based on Lens Imaging Learning Strategy State Transition Algorithm

Abstract: :Parameter identification of fractional-order chaotic power systems is a multidimensional optimization problem that plays a decisive role in the synchronization and control of fractional-order chaotic power systems. In this paper, a state transition algorithm based on the lens imaging learning strategy is proposed for parameter identification of fractional-order chaotic power systems. Taking a fractional-order six-dimensional chaotic power system mathematical model as an example, the mathematical model and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Step4: Map the points of the chaotic sequence back to the original space according to the following equation (Ai et al, 2023):…”
Section: Chaos Initializationmentioning
confidence: 99%
“…Step4: Map the points of the chaotic sequence back to the original space according to the following equation (Ai et al, 2023):…”
Section: Chaos Initializationmentioning
confidence: 99%
“…The state space transition equation, a core concept in dynamic system theory, describes the evolution of system states over time, as shown in Figure 9. The design of the state transition equation in this research is based on the following mathematical representation [77][78][79]:…”
Section: State Space Transition Equationmentioning
confidence: 99%
“…In addition, X. Li et al [11] conducted a chaos analysis on the six-dimensional model of the three-bus power system, which showed that due to the increase of load, the critical chaos oscillation tends to occur when the system is closer to the stable operation limit. Meanwhile, C. Ai et al [12] generated chaotic oscillations in a six-dimensional model of the power system by mechanical input power and model order, and proposed a state transition algorithm based on the lens imaging learning strategy to estimate the parameters of the chaotic model of the power system and reproduce its chaotic behaviour. Reference [13] analyzed the chaos of the sevendimensional power system model by the input mechanical power, and showed that there is a strong correlation between the power parameters and the chaos behavior.…”
Section: Introductionmentioning
confidence: 99%